Using genetic Potential of Teosinte from Collection of N.I.Vavilov Research Institute of Plant Industry to Expand Polymorphism of Prolific Maize (Zea mays L.) - Khatefov, E B; Appaev, S P (KnE Life Sciences, 2019)
A threat of genetic erosion of maize stimulate search for new sources to extend its polymorphism. Teosinte (Zea mays ssp. mexicana), being wild relative of maize, is easily intercrossed with maize and is characterized with a large potential of variability with respect to economically viable attributes, among them being prolific that is having more than one ear. Results are given of long-term selection of maize lines for the attribute of being prolific among the progeny of a hybrid between teosinte (int-350969) and maize. Selection was conducted against the background of soil preparation ideal for maize in a number of attributes that are congruent with prolificacy and synchronous blooming of all or at least majority of ears on a stalk. A wide diversity in the prolificacy of maize was obtained, with the prolificacy coefficient of up to kpr = 3.3 with a complicated mode of inheritance in hybrid progeny. Results of topcrossing with a single-ear sterile tester showed a specific reaction of the lines, provisionally dividing them into 4 groups by the nature of manifestation of the prolificacy in the hybrid progeny. It has been established that the prolific lines, which in hybridization with the single-ear tester are capable of forming more than one ear in the hybrid plant are of higher selective value. At that, it is important to take into account simultaneity of blooming of all the ears at a male plant. Observation of this principle leads to preservation of structure and evenness of ears in upper and lower layer, thus providing their productivity independent of layer on the stalk. Valuable prolific lines have been established for creation of prolific maize hybrids.